Removing the Confusion About What was Attributed to Ibn Hazm from Taking Analogies - a Fundamental Study - Saleh , Basim (Islamic Sciences Journal, 2023)
It was famous on the authority of Ibn Hazm that he denied analogy, then some of them claimed that he violated his approach, so he took it without realizing .That research came to restore things to their rightful place and proved through it that Ibn Hazm did not violate his approach, but rather confused of terminology because of his agreement with the judges, but not by analogy but by other evidence. This is what happens to many scholars without Without denunciation, such as their agreement to act on the interest and their difference in naming it, and in my research this I do not adopt a particular doctrine as much as it is a statement of the issue and presenting it with evidence.